ANALYSIS OF THE EFFECT OF AICC PARAMETERS VARIATION ON CNC MILLING MACHINES ON MACHINING TIME AND WORKPIECE ACCURACY - Sijabat, Henri Hendrik; Dharmajati, R Ariosuko (Universitas Mercu Buana, 2024)
The global market for Computer Numerical Control (CNC) milling machines continues to grow at a significant rate, with the automotive industry being the largest end-user. The Fanuc 31i controller is one of the leading controllers in the manufacturing industry. This controller has AI nano CNC features that support high-precision movements and high-speed NC program execution. The more understanding of the AICC (AI Contour Control) parameter settings can make a significant contribution to improvement of production efficiency and quality. This research is conducted to investigate the influence of changing the